Two Dimensional Path Planning with Static Polygon Obstacles Avoidance - Ramadhan, Duaa Ahmed; Rashid, Abdulmuttalib T.; Rashid, Osama T. (Iraqi Journal for Electrical and Electronic Engineering, 2020)
This paper presents the designing of path planning system in an environment contains a set of static polygon obstacles localized and distributed randomly by using differential drive mobile robot. In this paper the designed algorithm (two dimensional path planning algorithm) is proposed in order of investigate the path planning of mobile robot with free collision using the visibility binary tree algorithm. The suggested algorithm is compared with the virtual circles tangents algorithm in the time of arrival and the longest of the path to the target. The aim of this paper is to get an algorithm has better performance than the other algorithms and get less time of arrival and shortest path with free collision.